Are you hearing me? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Listening to Change: Paths of Communication. FAO. 1999. Video available in English and Spanish (PAL or NTSC formats), and in French (PAL or Secam). $20.00 / E19.50 FAO